Hong Kong–Macau Severe Hives and Angioedema Referral Pathway - Li, Philip H.; Au, Elaine Y. L.; Cheong, Si-Leong; Chung, Ling; Fan, Ka I.; Ho, Marco H. K.; Leung, Agnes S. Y.; Chung, Martin M. H.; Wong, Jane C. Y.; Coelho, Ricardo (Frontiers in Allergy, 2023)
A total of twenty-four CS were formulated; including four statements on classifications and definitions, seven statements on diagnosis, and thirteen statements on management and referral.Definitions for acute/chronic urticaria and severe CSU were stated. Unnecessary investigations and inappropriate medications were discouraged. The characteristics and recommend approach to suspected bradykinergic angioedema was specified. Stepwise treatment options using second-generation antihistamines, omalizumab or cyclosporin for patients with CSU were addressed, and the importance of access to HAE-specific medications was emphasized. Furthermore, an integrated referral pathway for patients with severe hives and angioedema was constructed.SHARP provides guidance for management and specialist referral of patients with severe hives and angioedema in Hong Kong and Macau.